The Social Face of Stigma: A Meta-Analysis of Gender, Support, and Living Environment in HIV/AIDS Perception - Utami, Indri Nur; Dewi, Rachael Saraswaty; Amalia, Rizky Nur Aprilianti; Murti, Bhisma; Veibiani, Nindita Arum (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: The stigma of society towards ODHA itself is influenced by various factors, where there are three factors that can be used as a benchmark, namely gender, place of residence, and social support. This study aims to estimate the magnitude of the influence of gender, social support and housing on the perception of stigma in people with HIV/AIDS, based on the results of a number of previous primary studies. Subject and Method: This study is a meta-analysis and systematic review study, with PICO, Population: ODHA patients (People with HIV/AIDS), Intervention: Women, low social support and village dwelling, Comparison: men, high social support and urban dwelling, Ooucome: HIV/AIDS stigma. Primary study searches used electronic databases: PUBMED, BMC, Scopus and Scient Direct published from 2012 to 2022. The keywords used are